Biomarker Development Trial of Satraplatin in Patients with Metastatic Castration-Resistant Prostate Cancer. (15th December 2022) - Liaw, Bobby C; Tsao, Che-Kai; Seng, Sonia; Jun, Tomi; Gong, Yixuan; Galsky, Matthew D; Oh, William K
Abstract: Background: In the phase III SPARC trial, satraplatin, an oral platinum analogue, demonstrated anticancer activity in men with metastatic castration-resistant prostate cancer (mCRPC). Repeat biopsies are uncommon in mCRPC, limiting the feasibility of tissue–based biomarkers. This phase II study sought to evaluate the feasibility and utility of blood–based biomarkers to identify platinum–sensitive mCRPC. Methods: Patients with mCRPC who had progressed on docetaxel were enrolled at a single center from 2011 to 2013. Subjects received satraplatin 80 mg/m 2 by mouth daily on days 1-5 and prednisone 5 mg PO twice daily, on a 35-day cycle. Serial peripheral blood samples were collected for biomarker assessment. Results: Thirteen docetaxel-refractory mCRPC patients were enrolled, with a median age of 69 years (range 54-77 years) and median PSA of 71.7 ng/mL (range 0.04-3057). Four of 13 patients (31%) responded to satraplatin (defined as a PSA decline of ≥30%). Responders demonstrated improved time to disease progression (206 vs. 35 days, HR 0.26, 95% CI, 0.02-0.24, P = .003). A 6-gene peripheral blood RNA signature and serum tissue inhibitor of metalloproteinase-1 (TIMP-1) levels were assessed as biomarkers, but neither was significantly associated with response to satraplatin. Conclusion: In this small series, one-third of mCRPC patients responded to platinum–based chemotherapy. Peripheral blood biomarker measurement is feasible in mCRPC, though the biomarkers we investigated were not associated with platinum response. Other biomarkers, such as DNA damage repair mutations, should be evaluated. Abstract : Repeat biopsies are uncommon in metastatic castration–resistant prostate cancer (CRPC), limiting the feasibility of tissue–based biomarkers. This article evaluates the feasibility and utility of blood–based biomarkers to identify platinum–sensitive mCRPC.